A wearable exhaling-oxygen-sensing mask based on piezoelectric/gas-sensing coupling effect for real-time monitoring and uploading lung disease information. (2nd June 2022) - Lin, Yuxing; Long, Zhihe; Liang, Shan; Zhong, Tianyan; Xing, Lili
Abstract: Comprehensive analysis of respiratory gases may provide noninvasive health monitoring of lung diseases, such as corona virus 2019 pneumonia. Here, a self-powered wearable mask has been fabricated for real-time monitoring and uploading exhaling oxygen information. Tetrapod ZnO (T-ZnO) nanostructures are hybridized with polyvinylidene fluoride (PVDF) that adhere to flexible fabric substrate on a mask. The piezoelectric effect of T-ZnO/PVDF is coupled with the gas sensing properties. The sensing unit can convert breath energy into piezoelectric signal without any external power supply, and the outputting piezoelectric voltage increases with increasing oxygen concentration, acting as the sensing signal. The sensing unit integrated with data processing module and wireless Bluetooth module can transmit the exhaling oxygen information to the mobile device, realizing real-time monitoring the oxygenation capacity of the lungs. This self-powered wearable approach can promote the lung diagnosis outside of clinical settings.